The Influence of Sight Words Instruction in Reading Fluency in Blended Learning Context. - AL MESAFRI, AAESHA ABDULLA (2022)
The action research takes a mixed method strategy to curry out demonstration and examination of the effects of Sight word instruction in reading skills in a blended learning context with year three students. The sub-objective was to demonstrate primary English teachers’ opinions on sight word instructions. The study context was in a privet school in Ras Al Khaimah, and it focused on the primary section. The sample size was thirty participants: twenty-two English primary teachers and eight students. The data collection that was used are questionnaires, Semi- Structured Interviews, and artefacts. The data collection was done through triangulation to enhance validity and reliability. The major findings were: 1) Using sight word instructions improves reading skills, especially comprehension and fluency skills. 2) Sight word instructions enhance the confidence of year three students. 3) Many English teachers in the UAE believe in the effects of sight word instructions. 4) Sight word instructions are ineffective if there is no support from other language teaching approaches. Finally, the study's limits are depicted, and further implications are supplied.